2013
DOI: 10.1364/ol.38.000395
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light trapping in the silicon substrate with plasmonic Ag nanocones

Abstract: Ag nanocone enhanced light trapping in the silicon substrate is numerically investigated. For a wide range of the dielectric spacer thickness, the normalized scattering cross section of the rear located particles is higher than that of the front located particles, which is contrary to previous reports. This design not only avoids the conflict with the detrimental Fano effect but is also beneficial to the rear located particles. The fraction of the incident light scattered into silicon is calculated. The path l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…From application point of view, it should be remembered that plasmonic-based photovoltaics demands thinning of the light-absorbing layers without sacrificing the absorption, which enables more efficient carrier collection and voltage generation. The light-trapping capability of Ag nanocones is interesting in this respect and proven theoretically by full field electromagnetic simulations [ 44 ]. Owing to their tunable plasmonic response, cone-like nanostructures of Ag are reported as the promising candidate for light trapping for photovoltaics and broadband antireflection properties [ 44 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From application point of view, it should be remembered that plasmonic-based photovoltaics demands thinning of the light-absorbing layers without sacrificing the absorption, which enables more efficient carrier collection and voltage generation. The light-trapping capability of Ag nanocones is interesting in this respect and proven theoretically by full field electromagnetic simulations [ 44 ]. Owing to their tunable plasmonic response, cone-like nanostructures of Ag are reported as the promising candidate for light trapping for photovoltaics and broadband antireflection properties [ 44 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The light-trapping capability of Ag nanocones is interesting in this respect and proven theoretically by full field electromagnetic simulations [ 44 ]. Owing to their tunable plasmonic response, cone-like nanostructures of Ag are reported as the promising candidate for light trapping for photovoltaics and broadband antireflection properties [ 44 46 ]. It should be further noted that Wehner et al found micro-cones, when Cu target was irradiated by 400 to 600 eV Hg ions assisted with Mo seeding (in sputtering plasma process) [ 27 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In plasmonic sensor fields, the narrower Fano peak width largely improves the sensitivity of localized surface plasmon resonance sensors [22]. In optical trapping fields, the Fano interference-induced force provides an ultrasensitive selection method for metal nanoparticles [23].…”
Section: Introductionmentioning
confidence: 99%
“…Not all probable factors associated with thin-film solar cells such as the optical properties of constituting materials and environmental stimuli [6,14] have been thoroughly considered in the optimization, and this paper is confined to the influence of size and shape of nanoparticles only. In addition to various randomly shaped structures [3,4], the effects of some primitive geometries such as cylinder, cone, sphere, and hemisphere on light trapping have been investigated extensively [3,4,8,15,16]. It was reported that the cylindrical and hemispherical particles have better performance than spherical particles [4].…”
Section: Introductionmentioning
confidence: 99%